If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -2(5 + -2p) = 2(p + -6) + -23 3p + (5 * -2 + -2p * -2) = 2(p + -6) + -23 3p + (-10 + 4p) = 2(p + -6) + -23 Reorder the terms: -10 + 3p + 4p = 2(p + -6) + -23 Combine like terms: 3p + 4p = 7p -10 + 7p = 2(p + -6) + -23 Reorder the terms: -10 + 7p = 2(-6 + p) + -23 -10 + 7p = (-6 * 2 + p * 2) + -23 -10 + 7p = (-12 + 2p) + -23 Reorder the terms: -10 + 7p = -12 + -23 + 2p Combine like terms: -12 + -23 = -35 -10 + 7p = -35 + 2p Solving -10 + 7p = -35 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. -10 + 7p + -2p = -35 + 2p + -2p Combine like terms: 7p + -2p = 5p -10 + 5p = -35 + 2p + -2p Combine like terms: 2p + -2p = 0 -10 + 5p = -35 + 0 -10 + 5p = -35 Add '10' to each side of the equation. -10 + 10 + 5p = -35 + 10 Combine like terms: -10 + 10 = 0 0 + 5p = -35 + 10 5p = -35 + 10 Combine like terms: -35 + 10 = -25 5p = -25 Divide each side by '5'. p = -5 Simplifying p = -5
| 90+30x=2500 | | 0.23*h+2.34=6.25 | | 8(9-5)= | | log(x+8)13=1 | | 27a^3b^3=-8 | | 2(t+2)=2 | | 4x+7(x-8)=4(x-7) | | (4*2)2*3=192 | | y^2+22y=-96 | | 5(3x-5)-3=5(x-5)+87 | | y^2+22y=-9696 | | 10x+17x-8+2=-9x+2-8 | | 5(3x-5)-3=5(x-5)+8 | | log(-3x^2+3x-5)=0 | | 2x+9y=145 | | 4-4x-x^2+x^3=0 | | 3x+6+x+5=90 | | logx=-1.5 | | x^4-14x^2=32 | | p^2+14=9p | | 6+55x=33x+10 | | -10x+5(0)=-50 | | 2x^3=100x^2 | | -60a^2b^2-7ab=-1 | | 0.3*c+4=19 | | 6+55x=333 | | -10(0)+5y=-50 | | log^4(8x)=6 | | 2x^3+50x^2=0 | | 7(3d-8)= | | 17x^2+16x+4= | | 2(n+5)=4n+10 |